Applied intermediate macroeconomics - Hoover, Kevin D., 1955- (Cambridge : Cambridge University Press, 2012)
This textbook offers a complete course in applied macroeconomics at the intermediate level that emphasizes the application of economic theory to real-world data and policy. Topics covered include national and international income, financial accounts, business cycles, financial markets, economic growth, labor markets, aggregate supply and demand, inflation, and monetary and fiscal policy. The text is unique in developing a detailed toolkit of elementary statistics and graphical techniques for economic data. A strength is its detailed treatment of national and international financial markets and the institutions of monetary and fiscal policy, which makes it especially helpful in understanding recent economic crises. The website for the text is found at http://www.appliedmacroeconomics.com.
Machine generated contents note: Part I. Introduction: -- Macroeconomics and the real world -- The National Accounts: -- The national accounts and the structure of the economy -- Understanding gross domestic product -- Measuring prices and inflation -- Trends and Cycles: -- Trends and cycles; Part IV. Financial Markets -- The financial system -- The behavior of interest rates -- The international financial system and the balance of payments -- Aggregate Supply: -- Aggregate production -- Economic growth -- The ideal labor market -- Unemployment and the labor market process; Part VI. Aggregate Demand -- An introduction to aggregate demand -- Consumption and investment: a deeper look -- Macroeconomic Dynamics -- The dynamics of output, unemployment, and inflation -- Macroeconomic Policy -- Monetary policy -- Fiscal policy -- Macroeconomic Data: A Guide to Working with Economic Data.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: Macroeconomics